Dual-energy spectral detector computed tomography differential diagnosis of adrenal adenoma and pheochromocytoma: Changes in the energy level curve, a phenomenon caused by lipid components? - Wang, Yu-li; Liu, Xiao-lei; Liao, Ze-bing; Lu, Xiao-mei; Chen, Ling-lin; Lei, Yi; Zhang, Han-wen; Lin, Fan (Frontiers in Endocrinology, 2023)
Background and objectives Pheochromocytoma and adrenal adenoma are common space-occupying lesions of the adrenal gland, and incorrect surgery may lead to adrenal crisis. We used a new method, dual-energy spectral detector computed tomography (SDCT), to differentiate between the two. Materials and methods We analysed the imaging images of patients with SDCT scans and pathologically confirmed adrenal adenomas (n=70) and pheochromocytomas (n=15). The 40, 70, and 100 KeV virtual monoenergetic images (VMIs) were reconstructed based on the SCDT arterial phase, and the correlation between the arterial/venous phase iodine concentration (AP-IC/VP-IC), the effective atomic number (Z-effect), the slope of the Hounsfield unit attenuation plot (VMI slope) and the pathological results was tested. The Shapiro−Wilk test was used to determine whether the above data conformed to a normal distribution. For parameters with P greater than 0.05, Student’s t test was used, and the Mann−Whitney test was used for the remaining parameters. A ROC curve was drawn based on the results. Results Student’s t test showed that the 40 KeV VMI and the VMI slope were both statistically significant (P<0.01). The Mann−Whitney U test showed that ID-A was statistically significant (P=0.004). ROC curve analysis showed that 40 keV VMI (AUC=0.818), AP-IC (AUC=0.736), difference (AUC=0.817) and VMI-Slope (0.817) could be used to differentiate adrenal adenoma from pheochromocytoma. Conclusion The effect of lipid components on SDCT parameters can be used to differentiate adrenal adenoma from pheochromocytoma.